Pengembangan Model Pembelajaran Manajemen P r oy e k Teknologi Informasi Berbasis Mu l tim e d i a - Ignatius Joko Dewanto; Sri Widiowati; Dwi Solaria Suharti (Universitas Tangerang Raya, 2021)
The background of the research problems written in this journal document is the difficulty of improving student learning achievement supported by the improvement of student cognitive, affective and psychomotor competencies, and supported by social competence and interrelation competencies between each student. The research method used in this study is to use research and development models, using Dick and Carey's learning design design. The research objective of developing a model of information technology project management materials with multimedia based is for learning needs in improving the competencies of students. Then, the results of research and development are models for the development of teaching materials, a set of teaching materials from the curriculum, GBPP, syllabus, RPS and also various media based on multimedia teaching materials. The contribution of research on the development of teaching materials models can be applied to other subjects which in turn can create a set of teaching materials that can be used by lecturers for the process of teaching and learning activities for one semester. Whereas for the follow-up of this research is to develop curriculum, enrich teaching materials, improve student competency and finally be able to increase campus brand in developing students who are qualified and have positive competitiveness in the era of modern globalization.